Three Junes - Glass, Julia, 1956- (New York : Anchor Books, 2003)
A novel that traces the lives of a Scottish family over a decade as they confront the joys and longings, fulfillments and betrayals of love in all its guises.
National Book Award winner for fiction, 2002.
Keywords: Scots -- United States -- Fiction; Fathers and sons -- Fiction; Gay men -- Fiction; Long Island (N.Y.) -- Fiction; Scotland -- Fiction; Psychological fiction; Domestic fiction